Instrumental Motivation and Self-Efficacy of Indonesian L2 Learners of English: Does Gender Play a Role? - Subekti, Adaninggar Septi; Sinaga, Yohanes Septian (VELES Voices of English Language Education Society, 2024)
Extensive research on second and foreign language learning suggests that gender can significantly influence language acquisition. While some studies indicate that female learners often outperform males in language tasks, the evidence is inconsistent, and findings may vary depending on the learning context. This highlights the need to explore further how gender interacts with other factors, such as motivation and self-efficacy, in shaping L2 learning outcomes. This study explores how gender affects learners' instrumental motivation and self-efficacy in learning English as a second language. A total of 144 L2 learners from non-English departments at a private university in Java, Indonesia, participated in this research, which utilized a survey design. Paper-based questionnaires were distributed to participants, who were recruited through convenience sampling. The findings revealed that female learners reported slightly higher levels of instrumental motivation (Mean female = 43.40) than male learners (Mean score-male = 42.78). However, the difference was not statistically significant, t= .86, p = .15. In terms of self-efficacy, male learners demonstrated marginally higher levels (Mean score-male = 47.71) than females (Mean score-female = 46.32), but again, this difference was not statistically significant, t= -1.48, p = .14. These findings suggest that, while gender differences in motivation and self-efficacy are often highlighted in L2 research, their impact may vary based on specific learning contexts. Further research is needed, incorporating additional learner variables, to clarify the complex relationship between gender and L2 learning outcomes.